Some Remarks on Burzyński’s Failure Criterion for Anisotropic Materials - P. SZEPTYŃSKI (Engineering Transactions, 2014)
Some misstatements appearing in the final form of the failure criterion formulation, de- rived from Burzyński’s hypothesis of material effort for anisotropic bodies, which haven’t been noticed in the literature as yet, are pointed out and discussed. Alternative interpretations of the results obtained by Burzyński are presented. Propositions of different formulation of the failure criterion, basing on original ideas of Burzyński, are given.